Etiology and Outcome of Patients with HIV Infection and Respiratory Failure Admitted to the Intensive Care Unit - Orsini, Jose; Ahmad, Noeen; Butala, Ashvin; Flores, Rosemarie; Tran, Truc; Llosa, Alfonso; Fishkin, Edward (Interdisciplinary Perspectives on Infectious Diseases, 2013)
Background. Although access to HAART has prolonged survival and improved quality of life, HIV-infected patients with severe immunosuppression or comorbidities may develop complications that require critical care support. Our objective is to evaluate the etiology of respiratory failure in patients with HIV infection admitted to the ICU, its relationship with the T-lymphocytes cell count as well as the use of HAART, and its impact on outcome. Methods. A single-center, prospective, and observational study among all patients with HIV-infection and respiratory failure admitted to the ICU from December 1, 2011, to February 28, 2013, was conducted. Results. A total of 42 patients were admitted during the study period. Their median CD4 cell count was 123 cells/μL (mean 205.7, range 2.0–694.0), with a median HIV viral load of 203.5 copies/mL (mean 58,676, range <20–367,649). At the time of admission, 23 patients (54.8%) were receiving HAART. Use of antiretroviral therapy at ICU admission was not associated with survival, but it was associated with higher CD4 cell counts and lower HIV viral loads. Twenty-five patients (59.5%) had respiratory failure secondary to non-HIV-related diseases. Mechanical ventilation was required in 36 patients (85.1%). Thirteen patients (31.0%) died. Conclusions. Noninfectious etiologies of respiratory failure account for majority of HIV-infected patients admitted to ICU. Increased mortality was observed among patients with sepsis as etiology of respiratory failure (HIV related and non-AIDS related), in those receiving mechanical ventilation, and in patients with decreased CD4 cell count. Survival was not associated with the use of HAART. Complementary studies are warranted to address the impact of HAART on outcomes of HIV-infected patients with respiratory failure admitted to ICU.